EFFECT OF INTERVAL TRAINING ON PHYSICAL FITNESS VARIABLES OF FOOTBALL PLAYERS (International Journal of Food and Nutritional Sciences, 2023)
The objective of the investigation was to determine the impact of interval training on the physical fitness parameters of football athletes. For this investigation, forty (40) state level football athletes aged between 14-16 years were arbitrarily chosen from Golden Star football club Kheri, Talwana. The participants were arbitrarily divided into two categories as the experimental group (soccer athletes) and control group. The exploratory group underwent a period training programme while no training was provided for the command group. The duration of instruction was six weeks in a timetable of weekly three days for alternating days. The information was gathered based on the chosen physical health factors prior to and following the exercise duration. The information gathered was examined by "t" examination and the degree of importance was established at 0.05 level. Data examination revealed noteworthy enhancement in the velocity, nimbleness, and stamina of the football athletes.